Interaction between L1 and L2 communicative language competences - Mihaljević Djigunović, Jelena (Array, 2006)
The paper focuses on a study whose aim was to look into interactions between L1 and L2 communicative language competences of EFL language users. The author looks into primary school (year 8) learners' performances on communicative language tests that measured both their L1 and L2 competences. The sample included close to 400 participants with differing starting age in EFL learning. The tests had the same underlying design in both languages. Results of L1 measures were compared with results on L2 tests. Findings were analyzed at several levels.